A two‐stage hue‐preserving and saturation improvement color image enhancement algorithm without gamut problem. Issue 1 (23rd September 2022) - Zhou, Datang; He, Gang; Xu, Kang; Liu, Chang
Abstract: A novel hue‐preserving and color enrichment color image enhancement algorithm without gamut problem is proposed in this paper. First, the pixel values of the input image are stretched to the edge of RGB color space to improve the saturation. Then, the pixel values are converted to the complementary color space for saturation enhancement, so that the whole method has no gamut problem and keeps the contrast intensity of the output picture unchanged. Experimental results demonstrate that the proposed algorithm can overcome the poor color effect of traditional methods in the condition of low exposure and can restore the picture color better. Besides, higher saturation can be achieved through the proposed algorithm than up‐to‐date color image enhancement methods.